Pendekatan Supply Chain Management Untuk Meningkatkan Daya Saing Pada Bisnis Bunga Segar - Cahyani, Rusnandari Retno (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
In global business, each company requires to provide cheap products, good quality and services, and appropriate customer orders. Supply chain management should be adopted by the company in order to survive and win the market competition. This study aims to investigate the implementation of supply chain management in a fresh flower business, to observe the benefit of adopting the supply chain management which is assessed from goods suppliers, and to evaluate the distribution implementation to the customer. Supply chain management approach is conducted by involving all the interactions among suppliers, manufacturers, distributors, and customers. The chain covers not only transportation, scheduling information, cash and credit transfer, but also the transfer of ideas, designs, and materials. This research is a qualitative descriptive study. In conclusion, it is shown that the supply chain management approach potentially improves the competitiveness of the fresh flower business.Keyword: Customer, Distribution, and Supply Chain Management